Fractions of a chloroform extract of ajenjo leaves (Artemisia mendozana DC. var. mendozana) inhibit the proliferation, viability and clonogenicity of B16-F0 melanoma cells - Millán, María Elisa; Marra, María Fernanda; Salvarredi, Leonardo Andres; Lizarraga, Emilio Fernando; Lopez, Luis Alberto (Instituto de Histología y Embriología, 2020)
Fil: Millán, María Elisa. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mendoza. Instituto de Histología y Embriología de Mendoza Dr. Mario H. Burgos. Universidad Nacional de Cuyo. Facultad de Ciencias Médicas. Instituto de Histología y Embriología de Mendoza Dr. Mario H. Burgos; Argentina